2022
DOI: 10.1093/milmed/usab553
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Emergency Department Visits That May Be Appropriate for Management in Non-Emergency Settings

Abstract: Background Emergency departments (EDs) continue to struggle with overcrowding, increasing wait times, and a surge in patients with non-urgent conditions. Patients frequently choose the ED for non-emergent medical issues or injuries that could readily be handled in a primary care setting. We analyzed encounters in the ED at the Brooke Army Medical Center—the largest hospital in the Department of Defense—to determine the percentage of visits that could potentially be managed in a lower cost, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…We used the information gathered in previous phases to pilot an alternate appointment scheduling system. 10 , 14 Previous studies have shown that ED overcrowding is a worldwide issue. 8 , 9 Phase 2 of this study involved interviewing patients to the ED, 35% of patients stated that their reasoning for reporting to the ED was the inability to get a timely appointment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the information gathered in previous phases to pilot an alternate appointment scheduling system. 10 , 14 Previous studies have shown that ED overcrowding is a worldwide issue. 8 , 9 Phase 2 of this study involved interviewing patients to the ED, 35% of patients stated that their reasoning for reporting to the ED was the inability to get a timely appointment.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 A previous study by some of these same authors had similar findings in the same ED at the Brooke Army Medical Center (BAMC). 10 Civilian EDs have a unique obligation to serve all patients in need without considering their ability to pay. 11–13 However, all of the requirements of the Emergency Medicine Transfer and Active Labor Act do not necessarily apply to the MHS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Staffing planification will form the key strategy of this optimization (11), and will be completed with other complementary strategies. These strategies will consider reorganization of the triage process (12), and the redirection of non-emergent cases (13), toward alternative unscheduled primary care services.…”
Section: Discussionmentioning
confidence: 99%